FRI0105 Abcb1and ABCG2 Drug-Efflux Transporters Function and Its Association with Disease Activity in A Cohort of Patients with Rheumatoid Arthritis. (10th June 2014) - Atisha-Fregoso, Y.; Fragoso-Loyo, H.; Jakez-Ocampo, J.; Lima, G.; Baños, M.; Pascual-Ramos, V.; Contreras-Yáñez, I.; Llorente, L.
Abstract : Background: Is not uncommon to observe that an important number of patients with rheumatoid arthritis (RA) have to withdraw or change treatment because of lack or loss of efficacy. Several mechanisms of treatment resistance, including the drug-uptake and drug-efflux transporters belonging to the superfamily of transporters multidrug-resistance (MDR) has been described that might explain this status. Among these transporters, ABCB1 (P- gp) and ABCG2 (BCRP) may have an important role for among its substrates some disease-modifying drugs such as prednisone and chloroquine (for ABCB1) and methotrexate and sulfasalazine (for ABCG2) are included. Objectives: To determine the ABCB1 and ABCG2 transporters activity in RA patients in remission compared with those that do not achieve remission. Methods: Patients at the early RA clinic cohort of our Institute, who meet the ACR/EULAR 2010 diagnosis criteria, were included. ABCB1 (P-gp) and ABCG2 (BCRP) functional activity was measured in peripheral mononuclear cells by flow cytometry. The percentage of cells able to extrude specific substrates for ABCB1 (daunorubicin) and ABCG2 (mitoxantrone) were recorded. The specificity of the assay was confirmed with specific inhibitors (verapamil for ABCB1 and KO143 for ABCG2). Thirty healthy controls were also evaluated to established normal values. The study was approved by our local ethics committee. Statistical analysis: Continuous variables were compared with Student t or Mann -Whitney U tests and categorical variables with chi square or Fisher exact test as appropriate. Results: We included 21 patients (all women) with a mean age of 36.9±11.7 years, with disease duration of 4.67±3.59 years. Ten patients had active and 11 inactive disease determined by DAS28 (mean 4.22±0.92 vs 1.25±0.66, p<0.001). There were no significant differences in age, disease duration (5.4±3.5 vs 4±3.7 years) or the use of methotrexate (80 vs 100%), antimalarials (30 vs 36.4%), sulfasalazine (40 vs 27.3%) or PDN (70 vs 72%) among active vs inactive patients.Only one inactive patient was positive for ABCB1 and none for ABCG2 while 5 active patients were positive for ABCB1 and ABCG2. The median percentage value of cells able to extrude daunorubicin in active patients was 3% (IQR 1-15.5%) vs 1 (IQR 0-1) in inactive patients (p=0.036) while the median percentage of cells that extruded mitoxantrone in active patients was 3% (IQR 0-10.5%) vs 0% (IQR 0-1) in the inactive patients (p=0.05). Conclusions: Patients with active RA have a higher functional activity of ABCB1 and ABCG2 transporters compared with those in remission independently of treatment and disease duration. Follow up of these patients is currently ongoing –and will be presented- to determine if the functional activity of these efflux pumps entails a higher risk of persistent activity or risk of RA reactivation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5268